Will the Role and Effectiveness of Agriculture, Animal Husbandry and Plantation Service Organization to Farmer Empowerment: A Study in Mungkajang District, Palopo City - Husni, Hilda Fitriani; Idawati; Taruna Shafa Arzam AR; Burhanuddin Harahap (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The development of the agricultural sector is one of the important pillars to increase national economic growth and community welfare. This study measures whether the role of the Agriculture Office is focused on the empowerment of farmers through the effectiveness of the organization in Mungkajang District, Palopo City. The research methodology used was quantitative by collecting data from farmer groups using a structured questionnaire using the Likert scale. The number of respondents was 102 members of farmer groups. The data was analyzed statistically inferentially using the Structural Equation Modeling (SEM) technique using the Smart-PLS application. The results of the study show that the research results obtained that the variable of Service Role (X) has a positive and significant effect on Farmer Empowerment (Y) in Mungkajang District, Palopo City; Organizational Effectiveness (Z) has a positive and significant effect on Farmer Empowerment (Y) in Mungkajang District, Palopo City; the role of the Service (X) has a positive and significant effect on the Effectiveness of the Organization (Z); and Role (X) has a positive and significant effect on Farmer Empowerment (Y) in Mungkajang District through the Organizational Effectiveness (Z) of the Palopo City Agriculture, Livestock, and Plantation Office. Sugestion is in the future, this research could be carried out on a larger scale, with the coverage of all farmer group in Palopo City. This would be accomplished by comparing farmer group in each regional work unit. This would make it possible to evaluate the role and effectiveness of the agriculture, livestock and plantation service organization in farmer empowerment.